Dependency of R2 and R2* relaxation on Gd‐DTPA concentration in arterial blood: Influence of hematocrit and magnetic field strength. (23rd November 2021) - van Dorth, Daniëlle; Venugopal, Krishnapriya; Poot, Dirk H. J.; Hirschler, Lydiane; de Bresser, Jeroen; Smits, Marion; Hernandez‐Tamames, Juan A.; Debacker, Clément S.; van Osch, Matthias J. P.
Abstract : Dynamic susceptibility contrast (DSC) MRI is clinically used to measure brain perfusion by monitoring the dynamic passage of a bolus of contrast agent through the brain. For quantitative analysis of the DSC images, the arterial input function is required. It is known that the original assumption of a linear relation between the R2 (*) relaxation and the arterial contrast agent concentration is invalid, although the exact relation is as of yet unknown. Studying this relation in vitro is time‐consuming, because of the widespread variations in field strengths, MRI sequences, contrast agents, and physiological conditions. This study aims to simulate the R2 (*) versus contrast concentration relation under varying physiological and technical conditions using an adapted version of an open‐source simulation tool. The approach was validated with previously acquired data in human whole blood at 1.5 T by means of a gradient‐echo sequence (proof‐of‐concept). Subsequently, the impact of hematocrit, field strength, and oxygen saturation on this relation was studied for both gradient‐echo and spin‐echo sequences. The results show that for both gradient‐echo and spin‐echo sequences, the relaxivity increases with hematocrit and field strength, while the hematocrit dependency was nonlinear for both types of MRI sequences. By contrast, oxygen saturation has only a minor effect. In conclusion, the simulation setup has proven to be an efficient method to rapidly calibrate and estimate the relation between R2 (*) and gadolinium concentration in whole blood. This knowledge will be useful in future clinical work to more accurately retrieve quantitative information on brain perfusion. Abstract : By adapting an open‐source simulation tool new insights on the relation between ΔR2 (*) and [Gd] in whole blood have been obtained and its dependency on physiological and MR parameters. The simulations showed good agreement with previously obtained in vitro data. For both gradient‐echo and spin‐echo sequences, the relaxivity increases with hematocrit value and field strength. This knowledge will be useful in future clinical work to more accurately calculate the arterial input function and therefore improve the quantitative analysis of DSC‐MRI.